Antibacterial Effect of Ozone on Cariogenic Bacteria and Its Potential Prejudicial Effect on Dentin Bond Strength-An In Vitro Study - Marta Santos; Flávia Leandro; Helena Barroso; António H. S. Delgado; Luís Proença; Mário Polido; Joana Vasconcelos e Cruz (MDPI AG, 2024)
Ozone is increasingly utilized in dental caries treatment due to its antibacterial properties. In a context of limited studies and no consensus on protocols, this research aims to assess ozone's antibacterial efficacy on cariogenic bacteria and its potential adverse impact on dentin bond strength. Streptococcus mutans, Streptococcus sobrinus, Lactobacillus casei, and Actinomyces naeslundii suspensions were exposed to 40 μg/mL of ozone gas and 60 μg/mL of ozonated water (80 s) via a medical ozone generator. Negative and positive control groups (chlorhexidine 2%) were included, and UFC/mL counts were recorded. To examine microtensile bond strength (µTBS), 20 human molars were divided into four groups, and class I cavities were created. After ozone application, samples were restored using an etch-and-rinse and resin composite, then sectioned for testing. The SPSS v. 28 program was used with a significance level of 5%. The µTBS results were evaluated using one-way ANOVA, Tukey HSD, and Games-Howell. Bacterial counts reduced from 106 to 101, but dentin µTBS was significantly impacted by ozone (ANOVA, p < 0.001). Despite ozone's attractive antibacterial activity, this study emphasizes its detrimental effect on dentin adhesion, cautioning against its use before restorative treatments.